Off‐label use of percutaneous pulmonary valved stents in the right ventricular outflow tract: Time to rewrite the label?. Issue 6 (12th February 2013) - Boshoff, Derize E.; Cools, Bjorn L.M.; Heying, Ruth; Troost, Els; Kefer, Joelle; Budts, Werner; Gewillig, Marc
<x xml:space="preserve">Abstract</x> Introduction Percutaneous pulmonary valve implantation is now considered feasible and safe. "Native" right ventricular outflow tract (RVOT), small diameter conduits (<16 mm) and relatively large RVOT with a dynamic outflow aneurysm are currently considered off‐label uses. Extending indications creates concerns of safety, ethics, reimbursement, and liability. Aim of study To report the safety and feasibility of off‐label application of percutaneous pulmonary valve implantation. Design Retrospective analysis of prospectively collected data. Patients and Methods Off‐label indications: conduit‐free RVOT or patients with an existing but undersized conduit. Results Twenty‐one Melody® valves and two Sapien® valves were successfully implanted in 23 patients (16.9 years; range 6.1–80.5 years). In 22 patients, prestenting was performed 4.8 months (range 0–69.2) before valve implantation (15 covered and 13 bare stents). Stent endothelial ingrowth was allowed for at least 2 months prior to implantation of the percutaneous valve if stent stability or sealing by the covering was presumed to be insufficient. Group 1 patients (n = 8) had a "conduit‐free" RVOT after transannular/infundibular patch and after prestenting underwent percutaneous pulmonary valve implantation (PPVI), with a final RVOT diameter of 21.5 mm (range 16–26 mm). Group 2 patients consisted of two elderly patients with pulmonary valve stenosis and severe RVOT calcifications. Group 3 (n = 13) had an existing conduit (nominal 15.9 ± 3.2 mm; range 10–20 mm). The conduit was augmented from 14.7 ± 3.5 to 20 ± 1.6 mm with PPVI. The RVOT preparation and valve implantations were uneventful. Conclusions PPVI is safe and feasible in selected patients with an off‐label indication. Creating an adequate "landing zone" by prestenting makes the procedure safe and predictable. Updating the indications for PPVI should be considered. © 2013 Wiley Periodicals, Inc.